With Great Power Comes Great Responsibility : Macroprudential Tools at Work in Canada - Krznar, Ivo (IMF Working Papers; Working Paper ;, 2014)
The goal of this paper is to assess the effectiveness of the policy measures taken by Canadian authorities to address the housing boom. We find that the the last three rounds of macroprudential policies implemented since 2010 were associated with lower mortgage credit growth and house price growth. The international experience suggests that-in addition to tighter loan-to-value limits and shorter amortization periods-lower caps on the debt-to-income ratio and higher risk weights could be effective if the housing boom were to reignite. Over the medium term, the authorities could consider structural measures to further improve the soundness of housing finance.